SANEAMENTO COMO DIREITO HUMANO E DEVER DO ESTADO: UMA ANÁLISE A PARTIR DO CONTEXTO DE MATO GROSSO DO SUL - TAÍS MARIANA LIMA PEREIRA (2022)
Sanitation is essential for a dignified human life, therefore, at the beginning of 21st century it was recognized as a human right on an international level, and consequently, it was perceived as a duty of the State. Furthermore, sanitation is highly related to the social, economic, and environmental tripod that establishes the ideal of sustainability, it is addressed in the Sustainable Development Goal 6 of the 2030 Agenda, established by the United Nations. The question that arises in this research is whether the domestic legal system and its jurisprudence, especially in Mato Grosso do Sul, address the problems and challenges of sanitation from the perspective of Human Rights and State’s duties. The hypothesis presented at the beginning of the research is that despite the progress that has been made, adjustments are needed in the domestic legal system and in its jurisprudence, both at national and state levels, so that sanitation is effectively treated as a human right. Thus, the general objective of this research is to verify if the problems and challenges related to sanitation are approached by domestic legislation and its jurisprudence, especially in Mato Grosso do Sul, in a way that sanitation is enforced as a human right. The first chapter intends to comprehend the concept of sanitation and its importance, as well as to know the genesis of the human right to sanitation and the minimal international standards of protection. The second chapter intends to examine sanitation in the Brazilian legal system, presenting the country’s current overview, and the study of sanitation from the perspective of public policies and public services, in an approach that seeks dialogue between International Human Rights and Administrative Law. Lastly, the third chapter addresses sanitation in the context of Mato Grosso do Sul, considering its social, environmental, and economic specificities, deepening the analysis at local level in the largest urban centers of the Intermediate Geographical Regions of the state (Campo Grande, Corumbá, Dourados), to verify state’s jurisprudence on issues that permeate the theme of sanitation. In conclusion, the hypothesis was confirmed, considering the general adoption of the international standards by the domestic legislation and jurisprudence, but there are remaining points that need attention and adjustments, for example, the impossibility of suspending the services in case of default by the user, the need to establish a vital minimum of water for human subsistence and the requirement of a positive performance of the companies that provide the service in favor of the human right to sanitation. The scientific method adopted is the hypothetical-deductive, based on a bibliographical and documentary research, guided by the post-positivist paradigm and with a dogmatic approach. Keywords: International Human Rights. Sustainable Development Goals. Sanitation. Public Policies. Public Services.